Factors that influenced Libyan teachers’ decisions in selecting materials for EFL reading classroom / Abdulhadi Masoud Alsanousi Aljadi... [et al.] - Alsanousi Aljadi, Abdulhadi Masoud; Mohd Ariff Albakri, Intan Safinas; Ismail, Noriah; Sarudin, Anida (UiTM Cawangan Johor, 2019)
Instructional materials have always been one of the key factors in enhancing teaching and learning. Hence, teachers assume the responsibilities in selecting effective materials to be used in the classroom. In order to decide instructional materials for the learners, teachers need to have the knowledge and understanding of selection criteria that will guide their decisions. This paper presents the factors that underlie Libyan EFL teachers’ decisions in selecting materials for reading lessons. The participants of this study are three Libyan English language teachers teaching in Libyan international schools in Malaysia. Lesson plans on the teaching of reading comprehension were referred to and interviews were conducted with the respective teachers to understand their decisions regarding materials used to teach reading comprehension. The findings showed that there are seven main factors that affect the participants’ choice of reading materials which are learners’ background, proficiency level, interest in reading, skill development, authenticity, level of difficulty and appealing content. This article provides a better understanding on the EFL teachers’ justifications of the materials selected in ensuring effective EFL reading lessons.